Modern ion plating technology : fundamentals and applications - Wang, Fuzhen; Wu, Junwei (Elsevier, 2023)
"Modern Ion Plating Technology: Fundamentals and Applications discusses the fundamental concepts of plasma physics in various coating technologies and explores its development and implementation into new technologies. Recent progress of technologies and products via ion plating will be introduced. The book begins with the treatment of vacuum physics, through plasma physics. It then presents the various forms of ion plating, before concluding with a section presenting examples of applications where ion plating is employed. Through the material presented in this book, the reader gains an understanding of the importance of ion plating technology to human progress and its various potential applications. Under the guidance of plasma physics knowledge, how to use electric and electromagnetic fields to control the space plasma will be critical to the development of new technology and systems" --